2007
DOI: 10.1002/jmv.20790
|View full text |Cite
|
Sign up to set email alerts
|

Role of surface promoter mutations in hepatitis B surface antigen production and secretion in occult hepatitis B virus infection

Abstract: The production, secretion, and localization of surface proteins of hepatitis B virus (HBV) and the ratio of large to small surface protein S was studied in HepG2 cells transfected with the wild-type and mutant pre-S1 and pre-S2/S promoters of HBV molecular clones 313.1 (GenBank accession no. AY161147) and 761.1 (GenBank accession no. AY161159) from two patients with occult HBV infection. Fusion constructs were made by in frame fusion of the wild-type surface gene to the mutant pre-S1 and pre-S2/S promoters and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 37 publications
1
23
0
1
Order By: Relevance
“…Alternatively, mutants resulted in decreasing the quantity of HBsAg secretion below the sensitivity of standard enzyme-linked immunosorbent assay but just enough for viral assembly may be the other explanation. Previously, Chaudhuri et al found similar pre-S variant from occult HBV carriers and demonstrated that deletion of S promoter would alter the ratio of large and small surface proteins and decrease the circulating HBsAg level [25,30] could normally replicate and be competent in HBsAg production [31]. Accordingly, they proposed that the host, rather than the viral factors, is responsible for occult HBV infection.…”
Section: Discussionmentioning
confidence: 96%
“…Alternatively, mutants resulted in decreasing the quantity of HBsAg secretion below the sensitivity of standard enzyme-linked immunosorbent assay but just enough for viral assembly may be the other explanation. Previously, Chaudhuri et al found similar pre-S variant from occult HBV carriers and demonstrated that deletion of S promoter would alter the ratio of large and small surface proteins and decrease the circulating HBsAg level [25,30] could normally replicate and be competent in HBsAg production [31]. Accordingly, they proposed that the host, rather than the viral factors, is responsible for occult HBV infection.…”
Section: Discussionmentioning
confidence: 96%
“…In transgenic mice, inhibition of HBsAg secretion has been related to the occurrence of cell injury mediated by interferon-␥ [24] . Furthermore, an association has been proposed between HBsAg secretion inhibition and occult HBV infection [25] . Among 1,220 HBV sequences available in databanks, only two (sequence accession numbers AY311358 [genotype F] and AF090842 [genotype A]) exhibited an amino acid variation at residue 215.…”
Section: Figmentioning
confidence: 99%
“…Besides, several investigations have described mutations clustering in the aforementioned key immunodominant regions of the HBsAg, which are able of decreasing the immune recognition of the virus, structural alteration and various mutations in genomic regulatory regions, leading to a strong reduction of HBsAg expression (4, 5, 7, 22, 24). In a functional survey by Sengupta et al in India, the production, secretion and localization of surface proteins of HBV were studied in HepG2 cells, transfected with the wild-type and mutant pre-S1 and pre-S2/S promoters of HBV molecular clones 313.1.…”
Section: Resultsmentioning
confidence: 99%